17+8(x-1)=-7

Simple and best practice solution for 17+8(x-1)=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17+8(x-1)=-7 equation:


Simplifying
17 + 8(x + -1) = -7

Reorder the terms:
17 + 8(-1 + x) = -7
17 + (-1 * 8 + x * 8) = -7
17 + (-8 + 8x) = -7

Combine like terms: 17 + -8 = 9
9 + 8x = -7

Solving
9 + 8x = -7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 8x = -7 + -9

Combine like terms: 9 + -9 = 0
0 + 8x = -7 + -9
8x = -7 + -9

Combine like terms: -7 + -9 = -16
8x = -16

Divide each side by '8'.
x = -2

Simplifying
x = -2

See similar equations:

| 19x+50=9(x+7) | | f(x)=3x^2-11x+28 | | 5y=-20x+10 | | Log[3]5-log[3]x=log[3]2 | | (2x+1)(x-3)(x-2)=0 | | ln(5x-9)=3 | | on(5x-9)=3 | | 16y^3-54=0 | | (x-5)(x^2-2x+7)= | | y^3-6y^2+11y=0 | | 12-6y=2y | | (4w+7)(5+w)=0 | | (6x-7)(6x+7)= | | 5+-= | | Log(3)5-log(3)x=log(3)2 | | (2x-2)(4x+8)= | | 375=15s+75 | | 5x+6-3x-3=6 | | 7(2a-4b)-3(4a-2b)= | | P+30.34= | | 3x^2-6x+4=13 | | 6x+3(2x+8)=120 | | 8x=2+y | | (22b-1)-7(3b+3)=-6 | | 5x(2x^2-3x+3)= | | C=15s+75 | | =90-70 | | 2y^2-y-36=0 | | 2x+25=3 | | 8x(9x+5)= | | 6s-17=-8+3s | | x*87=87 |

Equations solver categories